Ensinar e aprender no contexto da Educação Matemática: uma estratégia na intervenção da prática de ensinar em sala de aula - Santos, Allan Gomes dos (2020)
This work was initially motivated by our professional practice in basic education teaching, where we describe how the teaching of mathematics over time has evolved, showing us new behaviors between teacher and student in the intervention of teaching and learning in the classroom. class. The main objective is to propose a new mathematics teaching-learning strategy. Thus, we seek to investigate whether a new approach to mathematics teaching, based on mathematical education and contextualized in a negotiating / persuasive learning relationship, involves the learning strategy with the student stance of listening and listening without copying when the teacher is persuading and negotiating in your teach. Such an approach was based on the observation of the professional in the classroom. We used as action methodology the action research characterized by collaboration and negotiation among the members of the intervention. It was carried out with students from the final grades of elementary school and high school, where we sought to work on aspects in which we could verify and reflect for a transformation in teaching and learning. The formal and informal results show that the insertion of this teaching strategy creates a classroom environment with greater student participation and interaction, promotes empathy with the area of ​​study and cooperates for a more meaningful and enjoyable learning of mathematics, contributing to greater trust between the main agents of education, the teacher and the student.